2013
DOI: 10.1590/s0034-8910.2013047004267
|View full text |Cite
|
Sign up to set email alerts
|

Avaliacao da confiabilidade e validade do Indice de Qualidade da Dieta Revisado

Abstract: OBJECTIVE:Evaluate validity and reliability of the Brazilian Healthy Eating Index Revised according to the psychometric properties. METHODS:Cross-sectional study of a random sample of 2,375 individuals of both sexes, aged 12 or older from the city of São Paulo, Southeastern Brazil, drawn from the Health Survey carried out in 2003. Information on the population characteristics was acquired using a questionnaire. Food intake was obtained using 24h Recall, used to calculate the Brazilian Healthy Eating Index Revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0
14

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 17 publications
(11 reference statements)
4
30
0
14
Order By: Relevance
“…Another aspect demonstrated in this study was the higher ability of the BHEI of differentiating diet quality by gender, showing that females adhere more to healthy food recommendations, corroborating Andrade et al 23 , who published similar findings and claimed that this specific ability is an aspect of this index that reinforces its reliability and validity. The individual's age or age group could also reflect better food choices with rising age 1 , and in fact this study found that adults and older adults have healthier diets than adolescents.…”
Section: Discussionsupporting
confidence: 90%
“…Another aspect demonstrated in this study was the higher ability of the BHEI of differentiating diet quality by gender, showing that females adhere more to healthy food recommendations, corroborating Andrade et al 23 , who published similar findings and claimed that this specific ability is an aspect of this index that reinforces its reliability and validity. The individual's age or age group could also reflect better food choices with rising age 1 , and in fact this study found that adults and older adults have healthier diets than adolescents.…”
Section: Discussionsupporting
confidence: 90%
“…The BHEI-R is represented by a set of component-based foods, nutrients, and cooking ingredients with proven health implications, such as whole grains, unsaturated fats, fruits, and sodium 14 . The BHEI-R was considered a valid and reliable instrument to asses and monitor the diet quality of the Brazilian population 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the scores are estimated according to components' energy density, there is no information on energy intake adequacy, which would be important to prevent an energyunbalanced diet. Nevertheless, the BHEI-R was adapted 12 and validated 13 in Brazil to monitor dietary quality of ≥ 12 year-old individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the American RHEI 8 and the Brazilian Dietary Guidelines 11 , Previdelli et al 12 proposed the Brazilian Revised Healthy Eating Index (BHEI-R), aimed at characterizing both healthy and harmful aspects of the diet; additionally, Andrade et al 13 evaluated the validity and reliability of this index, concluding that it is reliable and structurally valid to monitor diet quality in Brazil. The BHEI-R has been used to summarize diet quality, highlighting key dietary characteristics, and is considered a useful tool in nutritional epidemiology 14 .…”
Section: Introductionmentioning
confidence: 99%